Aplikasi Bakteri Penambat N (BPN) dan Pupuk Kotoran Sapi (PKS) pada Fitoremediasi Tanah Tercemar Minyak Bumi - Ibnu Rizki Perdana; Tualar Simarmata; Pujawati Suryatmana (Composite : Jurnal Ilmu Pertanian, 2020)
Biostimulants plays an important role in the phytoremediation process of soil contaminated with hydrocarbon compounds. This experiment aims to determine the best treatment between N-fixing bacteria (BNF) and cow manure (CM) that can improve oil-polluted soil. The experiment was conducted in January-April 2019 at Kebun Percobaan Ciparanje Fakultas Pertanian Universitas Padjadjaran, Jatinangor, Sumedang, used a randomized block design method with four combinations (without BNF + without CM, Azotobacter sp. + without CM, without BNF + CM dose of 100% and Azotobacter sp. 4% + CM dose of 100%). The results showed there was not significant with control, except combination of without BNF + CM dose of 100% treatment could increase the population of Azotobacter sp. of 4.8 x 108 CFU/g, while Azotobacter sp. + without CM can increase the degradation of hydrocarbons and dry weight of ramie plants 0.1047 ppm/day and 40.433 g.